Analisis Pengelolaan Dana Desa Dalam Mengukur Kinerja Keuangan Di Desa Bandar Klippa Kecamatan Percut Sei Tuan - Pandapotan Ritonga; Zulham Afandi Saragi (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2026)
This study aims to examine village fund management and assess the financial performance of Bandar Klippa Village using the "value for money" method as a performance indicator. A descriptive method was employed, utilizing data from the Village Budget (APBDes) realization reports for the years 2017–2021. The results indicate that village fund management in Bandar Klippa Village (Percut Sei Tuan District, Deli Serdang Regency) complies with Ministry of Home Affairs regulations, although there were delays in reporting APBDes implementation to the Regent. Regarding the value-for-money method, the economy ratio fell into the "economical" category; however, the efficiency ratio was classified as "uneconomical" because realized expenditures exceeded received revenues. Finally, the effectiveness ratio was classified as "effective," as it maintained a 100% rate over the five-year period, demonstrating the village government's success in meeting planned revenue realization targets